2011
DOI: 10.1016/j.jmmm.2011.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of spinel FeCr2S4 in high magnetic field

Abstract: We studied temperature and magnetic field dependence of magnetization, M(T ) and M(B), on thiospinel FeCr 2 S 4 . We observed a step-like anomaly at T OO ∼ 9 K for M(T ) attributed to an orbital order transition in magnetic field 0 < B ≤ 7 T. Furthermore, also for M(B), an step-like anomaly appears at B c ∼ 5.5 T below T OO . This suggests an existence of a magnetic phase boundary at B c in T < T OO . Because the anomaly at B c of M(B) exists in the orbital ordered phase, the spin structure of FeCr 2 S 4 in T … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Moreover, recent reports have indicated modifications to the bulk magnetic properties of FeCr 2 S 4 under large applied magnetic fields in this temperature range. [31,40] Neutron diffraction was performed on FeCr 2 S 4 under external applied magnetic fields of up to 7.5 T in order to investigate a potential link between orbital order, the magnetic and crystal structures and external fields. In particular, deviations in the magnetic and crystal structure were studied by performing Rietveld refinement of the lattice and magnetic moment parameters of the Fe 2+ and Cr 3+ -ions.…”
Section: Neutron Diffractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent reports have indicated modifications to the bulk magnetic properties of FeCr 2 S 4 under large applied magnetic fields in this temperature range. [31,40] Neutron diffraction was performed on FeCr 2 S 4 under external applied magnetic fields of up to 7.5 T in order to investigate a potential link between orbital order, the magnetic and crystal structures and external fields. In particular, deviations in the magnetic and crystal structure were studied by performing Rietveld refinement of the lattice and magnetic moment parameters of the Fe 2+ and Cr 3+ -ions.…”
Section: Neutron Diffractionmentioning
confidence: 99%
“…The successful refinement of the FeCr 2 S 4 magnetic structure indicated that the spin-only moments are reduced from expected values of −4.2 µ B for Fe 2+ with S = 2 and g = 2.1 and 3.0 µ B for Cr 3+ with spin S = 3/2 and g = 2. Moreover, recent reports have indicated modifications to the bulk magnetic properties of FeCr 2 S 4 under large applied magnetic fields in this temperature range [31,40].…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…To date, much effort has been devoted to the experimental and computational study of physical properties of spinel compounds as a function of pressure (Kiefer et al 1997;Nestola et al 2002;Levy et al 2003;Reichmann and Jacobsen 2006), temperature (Askarpour et al 1993;Andreozzi et al 2000;Suzuki et al 2000), and at high magnetic and electric fields (e.g., Hong and Yoo 2006;Ito et al 2011). Nevertheless, there are still many open issues regarding the dependencies of the physical properties of spinels as a function of composition and crystal-chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…1. The ZFC, FC2 and FC3 curves are adapted from experimental results [49][50][51][52] and the rest ones, FC1 and FC4, are phenomenological extrapolations. The Néel temperature is T N = 170K.…”
mentioning
confidence: 99%